2020
DOI: 10.1093/femsec/fiaa256
|View full text |Cite
|
Sign up to set email alerts
|

Stream sediment bacterial communities exhibit temporally-consistent and distinct thresholds to land use change in a mixed-use watershed

Abstract: Freshwater ecosystems are susceptible to biodiversity losses due to land conversion. This is particularly true for the conversion of land from forests for agriculture and urban development. Freshwater sediments harbor microorganisms that provide vital ecosystem services. In dynamic habitats like freshwater sediments, microbial communities can be shaped by many processes, although the relative contributions of environmental factors to microbial community dynamics remain unclear. Given the future projected incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…During their study, Pingram et al (2020) showed a near‐linear relationship between cotton strips decomposition and gradients of both native vegetation cover (negative relationship) in the catchment and LUS. Multiple studies have demonstrated the influence of the surrounding landscape on stream bacterial community composition (Martin et al, 2020; Simonin et al, 2019) and have identified taxa that are abundant in streams impacted by urban and agricultural inputs (Laperriere et al, 2020). The indicator taxa in EHC‐D were also associated with increased temperature, possibly linked with less forested riparian margins, increased light, and warmer surface run‐off.…”
Section: Discussionmentioning
confidence: 99%
“…During their study, Pingram et al (2020) showed a near‐linear relationship between cotton strips decomposition and gradients of both native vegetation cover (negative relationship) in the catchment and LUS. Multiple studies have demonstrated the influence of the surrounding landscape on stream bacterial community composition (Martin et al, 2020; Simonin et al, 2019) and have identified taxa that are abundant in streams impacted by urban and agricultural inputs (Laperriere et al, 2020). The indicator taxa in EHC‐D were also associated with increased temperature, possibly linked with less forested riparian margins, increased light, and warmer surface run‐off.…”
Section: Discussionmentioning
confidence: 99%
“…30,32 Previous research also demonstrated that in-stream physiochemistry such as pH is correlated with E. coli concentrations and that chloride concentrations, likely resulting from road salts, are negatively correlated with E. coli. 30 Further, in-stream sediment microbial communities 33 and their correlation with land-use patterns have also been reported. 34 However, the impact of biotic factors (multiple fecal sources) and abiotic factors (landuse and in-stream physiochemical parameters) on the occurrence and persistence of ARGs has never been examined.…”
Section: ■ Introductionmentioning
confidence: 91%
“…coli . Further, in-stream sediment microbial communities and their correlation with land-use patterns have also been reported . However, the impact of biotic factors (multiple fecal sources) and abiotic factors (land-use and in-stream physiochemical parameters) on the occurrence and persistence of ARGs has never been examined.…”
Section: Introductionmentioning
confidence: 99%
“…Freshwater streams receive water from the adjacent land, making them especially vulnerable to the impacts of land-cover change, such as conversion of tropical forest to cattle pasture. Studies have shown that a range of stream properties can vary with a changing landscape, including water temperature, total dissolved solids, and water flow paths 10 12 . Further questions regard the extent to which stream microbial community diversity and structure is maintained or can recover as forests are allowed to regenerate on surrounding land and the tradeoffs made when managing land for livelihoods and other ecosystem services.…”
Section: Introductionmentioning
confidence: 99%